Generalized Hyperbolic Function Solution to a Class of Nonlinear Schrödinger-Type Equations - Zeid I. A. Al-Muhiameed; Emad A.-B. Abdel-Salam (Journal of Applied Mathematics)
With the help of the generalized hyperbolic function, the subsidiary ordinary differential equation method is improved and proposed to construct exact traveling wave solutions of the nonlinear partial differential equations in a unified way. A class of nonlinear Schrödinger-type equations including the generalized Zakharov system, the Rangwala-Rao equation, and the Chen-Lee-Liu equation are investigated and the exact solutions are derived with the aid of the homogenous balance principle and generalized hyperbolic functions. We study the effect of the generalized hyperbolic function parameters p and q in the obtained solutions by using the computer simulation.